Properties of milled zingiber officinale rosc (ginger) rhizome powder to coarse, fine and nano sizes and its effects on the storage stability of spent hen chicken / Norhidayah Abdullah - Abdullah, Norhidayah (Institute of Graduate Studies, 2017)
Z. officinale Rosc. (ginger) has been globally used and known to possess beneficial health properties due to the presence of various bioactive compounds. However, the poor absorption of these bioactive compounds is due to low water solubility, large particle size and complex chemical structure had restricted its bioactivity. The nanotechnology process has been reported as an advanced technology recently applied in food materials to increase the water solubility and improve bioactivity of the active ingredients. However, study on nanoparticle herbs is lacking, hence this study was conducted with the aimed to investigate the effect of nanotechnology process on physicochemical properties of nanoparticle Z. officinale rhizome powder. A study on the effect of this powder as a marinating agent on the storage stability of spent hen meat was also conducted. Physicochemical changes were determined using laser diffraction technique, Field Emission Scanning Electron Microscope (FESEM), The Fourier Transmittance IR (FTIR) and X-ray diffraction (XRD). Antioxidant content was estimated by Total Phenolic Content (TPC) and Total Flavonoid Content (TFC) while antioxidant activity was performed via ABTS Cation Decolorisation Assay (ABTS), DPPH Radical Scavenging Activity (DPPH) and Ferric Reducing Antioxidant Power (FRAP) assays..